How should Britain's government spending and tax burdens be measured? A historic perspective on the 2009 budget forecasts - David B. Smith (Institute of Economic Affairs (IEA), 2009)
In the 24th IEA Discussion Paper, David B. Smith takes an historical perspective on the 2009 Budget forecasts. His analysis concludes that the budget deficit will reach levels that are unprecedented in peacetime.The government's preferred market-price GDP measure overstates national output because it is reported gross of indirect taxes and subsidies. Factor-cost GDP, which excludes all indirect taxes and subsidies, is a far better measure for analysing the government spending burden.Using this better measure of national income, the 2009 Budget projections imply that the ratio of general government expenditure to national income will rise to 53.4% in 2010, the highest ratio since World War II and 6.9% above the peak recorded in World War I. The ratio of public expenditure to private spending, which was 92.4% in 2008, will rise to 107% in 2009 and 114.5% in 2010 - the highest burden since 1945.Also using the factor-cost measure, public sector net borrowing is projected to increase from 8% of national income in 2008-09, to 14.1% in 2009-10, and 13.5% in 2011-12.There must be serious doubt whether deficits on this scale can be financed in a non-inflationary manner, without very large capital inflows from abroad. It is hard to see why such inflows should be forthcoming now that the British economy has become so highly taxed by international standards.The deficit can only partly be explained by the onset of severe recession. The ratio of government spending to GDP rose from 41.8% in 1999 to 45.8% in 2007 before the downturn commenced.The rise in non-productive spending as a share of GDP since 2000 is likely to have cut the UK's sustainable growth rate by some 1.0 to 1.7% per annum. Such a drop in productive potential will have reduced investment returns, which may have lead to a reduction in the supply of capital and contributed to the current crisis.Britain's current profligate fiscal policies are more likely to lead to 1970s-style stagflation than cure the recession.When Keynes wrote his General Theory in 1936 the ratio of general government expenditure to national output was only slightly over one half of the figure officially projected for next year. His correspondence after World War II suggests that Keynes would not have advocated further increases in the government spending ratio from such a high starting point.
Keywords: 330; Public budget; Public revenue; Tax burden; Public expenditure; Measurement; Great Britain; Öffentlicher Haushalt; Öffentliche Einnahmen; Steuerbelastung; Öffentliche Ausgaben; Messung; Großbritannien